2013
DOI: 10.1016/j.lfs.2012.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Analytical surveillance of emerging drugs of abuse and drug formulations

Abstract: Uncontrolled recreational drugs are proliferating in number and variety. Effects of long-term use are unknown, and regulation is problematic, as efforts to control one chemical often lead to several other structural analogs. Advanced analytical instrumentation and methods are continuing to be developed to identify drugs, chemical constituents of products, and drug substances and metabolites in biological fluids. Several mass spectrometry based approaches appear promising, particularly those that involve high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Studies used THC and the following five SCs reported to have higher efficacy than THC at CB 1 Rs (in order from purported highest to lowest efficacy): A-834,735 degradant (A-834,735D), WIN55,212-2 and CP55,940, JWH-073, and CP47,497 (Breivogel et al, 1998;Griffin et al, 1998;Auwärter et al, 2009;Atwood et al, 2011;Thomas and Wiley, 2014;Grim et al, 2016).The m opioid receptor agonist morphine and dopamine receptor antagonist chlorpromazine were tested as controls that were expected to produce in vivo effects independent of CB 1 R density. A-834,735D, WIN55,212-2, CP47,497, JWH-073, and chlorpromazine were obtained from Cayman Chemical (Ann Arbor, MI), and morphine, THC, and CP55,940 were generously supplied by the National Institute on Drug Abuse Drug Supply Program.…”
Section: Drugsmentioning
confidence: 99%
“…Studies used THC and the following five SCs reported to have higher efficacy than THC at CB 1 Rs (in order from purported highest to lowest efficacy): A-834,735 degradant (A-834,735D), WIN55,212-2 and CP55,940, JWH-073, and CP47,497 (Breivogel et al, 1998;Griffin et al, 1998;Auwärter et al, 2009;Atwood et al, 2011;Thomas and Wiley, 2014;Grim et al, 2016).The m opioid receptor agonist morphine and dopamine receptor antagonist chlorpromazine were tested as controls that were expected to produce in vivo effects independent of CB 1 R density. A-834,735D, WIN55,212-2, CP47,497, JWH-073, and chlorpromazine were obtained from Cayman Chemical (Ann Arbor, MI), and morphine, THC, and CP55,940 were generously supplied by the National Institute on Drug Abuse Drug Supply Program.…”
Section: Drugsmentioning
confidence: 99%
“…The proper handling, storage, separation, and detection of these novel chemicals in complex matrix and elucidation of the exact chemical structure often requires the use of several sophisticated analytical instruments and laboratory techniques and the interpretation of complex datasets that together can provide sufficient integrated molecular information to confirm identity. Moreover, the analytical methods used for legal or forensic purposes must also be validated and shown to provide suitably accurate, specific, and reliable information, which adds to the cost and complexity involved in either targeted or broad-spectrum methods [ 111 , 112 ]. Finally, in vitro and in vivo laboratory studies are increasingly used to provide evidence that novel chemicals that are being encountered on the illicit market are cannabimimetics that bind to and activate CB 1 cannabinoid receptors [ 113 , 114 , 115 ].…”
Section: The Ultimate Diversion Of Cannabimimetic Indoles: Spice/k2mentioning
confidence: 99%